2017
DOI: 10.1002/ppul.23763
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hearing and vestibular loss in cystic fibrosis patients exposed to aminoglycosides

Abstract: These results suggest that monitoring hearing alone is insufficient to detect ototoxicity in CF patients being treated with systemic AGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…93 CF patients may be more prone to the vestibular toxicity of inhaled amikacin due to chronic exposure to parenteral aminoglycosides to treat Pseudomonas infections. 94 In the CONVERT study, which enrolled patients with amikacin-susceptible MAC as well as sputum positivity despite at least 6 months of guideline-based therapy (GBT), 29% of patients in the ALIS-GBT arm compared with 8.9% in the GBT-only arm achieved culture conversion. Patients with CF were excluded from this study; however, 62.5% had underlying bronchiectasis, which allows for some extrapolation between the two groups.…”
Section: Drugs Of Emerging Efficacy Inhaled Amikacinmentioning
confidence: 99%
“…93 CF patients may be more prone to the vestibular toxicity of inhaled amikacin due to chronic exposure to parenteral aminoglycosides to treat Pseudomonas infections. 94 In the CONVERT study, which enrolled patients with amikacin-susceptible MAC as well as sputum positivity despite at least 6 months of guideline-based therapy (GBT), 29% of patients in the ALIS-GBT arm compared with 8.9% in the GBT-only arm achieved culture conversion. Patients with CF were excluded from this study; however, 62.5% had underlying bronchiectasis, which allows for some extrapolation between the two groups.…”
Section: Drugs Of Emerging Efficacy Inhaled Amikacinmentioning
confidence: 99%
“…Gentamicin has, e.g., been reported to be associated with no safe serum level for vestibulotoxicity [ 5 ]. In a prospective study of patients receiving variable dosing of aminoglycosides, vestibular dysfunction was reported to be more frequent than auditory dysfunction [ 18 ].…”
Section: Aminoglycoside Antibioticsmentioning
confidence: 99%
“…In a retrospective single‐center study of 71 patients 30 days to 18 years of age, the rate of acute kidney injury was significantly higher in patients receiving Piperacillin‐tazobactam (55%) compared to those receiving cefepime (13%) in addition to tobramycin and vancomycin . In a single‐center study of CF patients over 8 years of age who had been on aminoglycosides, 23% had hearing loss on audiologic evaluation . However, evaluation of the vestibular system showed that 79% had involvement, leading to a recommendation for addition of vestibular evaluation in patients receiving aminoglycosides.…”
Section: Extrapulmonary Complicationsmentioning
confidence: 99%